Mood Disturbances, Anxiety, and Impact on Quality of Life in Patients Admitted to Epilepsy Monitoring Units - Rocamora, Rodrigo; Chavarría, Beatriz; Pérez, Eva; Pérez-Enríquez, Carmen; Barguilla, Ainara; Panadés-de Oliveira, Luisa; Principe, Alessandro; Zucca, Riccardo (Frontiers in Neurology, 2021)
Introduction: The overall combined prevalence of anxiety and depression in patients with epilepsy has been estimated at 20.2% and 22.9%, respectively, and is considered more severe in drug-refractory epilepsy. Patients admitted to Epilepsy Monitoring Units constitute a particular group. Also, patients with psychogenic non-epileptic seizures can reach more than 20% of all admissions. This study aims to characterize these disorders in a large cohort of patients admitted for evaluation in a tertiary epilepsy center. Materials and methods: The study was conducted among 493 consecutive patients (age: 38.78±12.7, 57% females) admitted for long-term VEEG from January 2013 to February 2021. Demographic, clinical, and mood disorder patients’ data were collected. Anxiety and depression symptoms were assessed through the Hospital-Anxiety-Depression-Scale (HADS-A and HADS-D), the State-Trait-Anxiety-Inventory (STAI), and Beck-Depression-Inventory (BDI-II). Quality of life was determined using the QOLIE-10. Patients were divided into three groups: PWE (n=395), PNES (n=56), and combined (n=33). A univariate and multivariate regression analysis was performed for variables associated with quality of life. Results: Of 493 patients, 45.0% had structural etiology, and considering epilepsy classification, 43.6% were of temporal lobe origin. 32.45% of patients had a previous psychiatric history. 49.9% of patients had depressive symptoms in BDI and 30.9% according to HADS-D, 56.42% and 52.63% of patients presented pathological anxiety scores in STAI-T and STAI-S, respectively 44.78% according to HADS-A. PNES and combined groups revealed a higher incidence of pathologic BDI scores (64.29% and 78.79%, p<.001), as well as pathologic HADS-A scores (p=0.001). Anxiety and depression pathologic result more prevalent in females, HADS-A (Females=50.7%, Males=36.8%; p=0.0027) and BDI>13 (w=56.6%, m=41.0%; p=0.0006). QOLIE-10 showed that 71% of the patients had their quality of life affected, with significantly higher scores in the combined group than in epilepsy and PNES groups (p=0.0015). Conclusions: Subjective anxiety, depression, and reduced quality of life are highly prevalent in patients with refractory epilepsy. These symptoms are more evident when PNES are associated with epilepsy and more severe between female patients. Most of the cases were not previously diagnosed. These factors should be considered in everyday clinical practice, and specific approaches might be adapted depending on the patient’s profile.